2021
DOI: 10.1136/tsaco-2020-000591
|View full text |Cite
|
Sign up to set email alerts
|

Early ventilator liberation and decreased sedation needs after tracheostomy in patients with COVID-19 infection

Abstract: BackgroundSince the outset of the coronavirus disease 2019 (COVID-19) pandemic, published tracheostomy guidelines have generally recommended deferral of the procedure beyond the initial weeks of intubation given high mortality as well as concerns about transmission of the infection to providers. It is unclear whether tracheostomy in patients with COVID-19 infection facilitates ventilator weaning, and long-term outcomes are not yet reported in the literature.MethodsThis is a retrospective study of tracheostomy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 28 publications
1
13
0
Order By: Relevance
“…Early tracheostomy in the literature has been defined as less than ten days, and sometimes even less than 96 h. 20 Decannulation (46.8%) and mortality (22.7%) rates are also in line with data reported from other centers. 24,33 We did not see a significant difference in decannulation or mortality in the early versus late groups. We suspect this is related to the variability of critical illness and our relatively small cohort of patients.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Early tracheostomy in the literature has been defined as less than ten days, and sometimes even less than 96 h. 20 Decannulation (46.8%) and mortality (22.7%) rates are also in line with data reported from other centers. 24,33 We did not see a significant difference in decannulation or mortality in the early versus late groups. We suspect this is related to the variability of critical illness and our relatively small cohort of patients.…”
Section: Discussionmentioning
confidence: 53%
“…22,23 Small, single-center studies in COVID-19 have shown decreased sedation medication pre- and post-tracheostomy. 24,25 As we gained a firm understanding of safe procedure performance, the COVID-19 pandemic provided a unique opportunity to assess outcomes in tracheostomy given the increased tracheostomy volume.…”
Section: Introductionmentioning
confidence: 99%
“…A subgroup of patients with COVID‐19‐related severe acute respiratory failure may require prolonged periods of mechanical ventilation (MV) in the intensive care unit (ICU). Performing tracheostomies in such patients may decrease sedation requirements, facilitate ventilator weaning, and early rehabilitation 1 . However, ongoing concerns remain surrounding the transmission of SARS‐CoV‐2 from patients to healthcare workers (HCWs) during the tracheostomy procedure.…”
Section: Introductionmentioning
confidence: 99%
“…Performing tracheostomies in such patients may decrease sedation requirements, facilitate ventilator weaning, and early rehabilitation. 1 However, ongoing concerns remain surrounding the transmission of SARS‐CoV‐2 from patients to healthcare workers (HCWs) during the tracheostomy procedure.…”
Section: Introductionmentioning
confidence: 99%
“…Prior to the pandemic, the outcomes of early versus late tracheostomy were investigated in several randomized clinical trials, and the pandemic added new urgency to question of optimal timing. 35 The data demonstrate that earlier tracheostomy can bring several important benefits to the patient and the healthcare system: tracheostomy reduces sedation requirements, 6 decreases requirement for invasive ventilation, 7 shortens ICU length of stay, 8 decrease incidence ventilator-associated pneumonia, 9 and alleviates risk of laryngeal injury associated with prolonged trans-laryngeal intubation of the trachea. 10 Notably, tracheostomy also eases the burden on critical care resources during surges.…”
mentioning
confidence: 99%